Immunocytochemical localization of group III metabotropic glutamate receptors in the hippocampus with subtype-specific antibodies - Bradley, SR (J Neurosci, 1996)
The metabotropic glutamate receptors (mGluRs) mGluR4 and mGluR7 have been postulated to serve as presynaptic autoreceptors in the hippocampal formation. The cellular and synaptic localization of these proteins in the hippocampus, however, is not known. Polyclonal antibodies that specifically react with mGluR4a or mGluR7 were produced and used for immunocytochemical localization of these receptor proteins. Immunoblot analysis with mGluRs expressed in stably transfected baby hamster kidney cells suggests that each of the antibodies reacts specifically with the appropriate mGluR subtype but not with other mGluRs. Both antibodies recognized native proteins in rat brain with molecular weights similar to the molecular weights of the bands in mGluR-transfected cell lines. The distribution of mGluR4a immunoreactivity was fairly uniform in all brain regions. Immunoreactivity for mGluR7 was variable in different brain regions and closely paralleled the previously reported distribution of mGluR7 mRNA. Immunocytochemistry with light and electron microscopy (EM) revealed that immunoreactivities for mGluR4a and mGluR7 are widely but differentially distributed throughout the hippocampal formation. Staining with antibodies directed against mGluR4a was intense in cell bodies and dendrites of pyramidal cells, granule cells, and scattered interneurons. Analysis at the EM level revealed postsynaptic mGluR4a localization at asymmetrical (presumably glutamatergic) synapses and presynaptic localization at both asymmetrical and symmetrical synapses. Immunoreactivity for mGluR7 revealed largely presynaptic localization of this receptor at asymmetrical but not symmetrical synapses. These data are consistent with a largely presynaptic role of mGluR7 in the hippocampus and suggest that mGluR4 may have both presynaptic and postsynaptic functions.